Comparison of high-flow oxygen therapy with standard oxygen therapy for prevention of postoperative pulmonary complications after major head and neck surgery involving insertion of a tracheostomy: a feasibility study. Issue 10 (December 2019) - Twose, P.; Thomas, C.; Morgan, M.; Broad, M.-A.
Abstract: Major operations on the head and neck that involve microvascular reconstruction and a tracheostomy are prolonged procedures with considerable postoperative risk. Postoperative pulmonary complications are common because of mechanical ventilation, immobility, and inadequate humidification. High-flow heated oxygen therapy (HFOT) may overcome some of these issues, but we know of no published studies to support its use. The aim of this single-site randomised controlled trial therefore was to explore its feasibility and safety in these patients. Twenty patients were randomised to have HFOT (10 patients) or standard oxygen therapy (10 patients). HFOT was used from cessation of mechanical ventilation until decannulation of the tracheostomy. The primary outcome was feasibility. The secondary outcome measures explored the incidence of postoperative pulmonary complications, achievement of milestones of weaning from the tracheostomy, and hospital length of stay. A total of 21 patients were consecutively recruited and all provided informed consent. One who did not require a tracheostomy was later excluded. All patients initially had the intervention as planned, and one was electively changed to the control group because of discomfort caused by the high-flow oxygen. There were no adverse events or safety concerns in either group. Secondary outcomes showed a reduction in the incidence of pulmonary complications in the HFOT group. The use of HFOT is safe and feasible in patients who have microvascular reconstruction of the head and neck and a tracheostomy.